Analisis Wacana Kritis pada Teks Revolusi Mental Joko Widodo - Ardana Putra, Vicky Fadly; Marantika, Eka Ririn; Khotimah, Khusnul; Syukri, Hanifullah (Aksara: Jurnal Bahasa dan Sastra, 2025)
The discussion in this research is about the critical discourse analysis model of Norman Fairclough. The purpose of this research is to understand the ideology, thoughts, or ideas of an official's discourse. The data source used from the text of Mental Revolution put forward by the Indonesian Presidential Candidate, Joko Widodo during the 2014 Indonesian Presidential election campaign with a length of 28 paragraphs. This research is included in qualitative descriptive research. The analysis process consists of three stages of Fairclough's theory: (1) Text Analysis, examining vocabulary, sentence structure, and the like to understand the meaning conveyed; (2) Discursive Practice, understanding how the text is produced to be consumed in a social context, as well as knowing how ideology is intertwined in a discourse; (3) Social Praxis, knowing the social impact of the text in the lives of Indonesian people. The data collection stage of the research uses the technique of recording data contained in words, sentences, and paragraphs contained in the Mental Revolution Text to obtain data. The theory used in this research is Norman Fairclough's critical discourse analysis theory. The results show that the text reflects the government's efforts to build a positive image through the narrative of national awakening, which in research can provide insight into how language is used to shape public perceptions and direct the public to support government policies. The text's conclusion of Jokowi's Mental Revolution discusses Joko Widodo's dream to change the mentality of the people in Indonesia to become a nation that stands on its own feet, but the reality has not been achieved until now.Keywords: Critical Discourse, Mental Revolution, Joko Widodo, Text